Experimental investigation and molecular dynamics simulations of the effect of processing parameters on the filling quality of injection‐molded micropillars. Issue 10 (4th August 2021) - Weng, Can; Sun, Huijie; Lai, Jun; Liu, Jiezhen; Zhai, Zhanyu
Abstract: Microinjection molding has been attracting increasing attention and application in fabricating products with functional surface microstructures. The processing parameters, packing pressure, and melt temperature have important effects on the filling quality. In order to study the mechanisms of the packing pressure and melt temperature on the filling quality of micropillars, a simulation model of injection molding of nanopillars was constructed by molecular dynamics software and a series of injection molding experiments of micropillars were carried out in this paper. Subsequently, the mechanisms were analyzed qualitatively. The results showed that the frozen layers were formed at the interface between the polymer melt and mold under the action of heat transfer, which prevented effective filling of the polymer melt. The filling quality of the micropillars could be improved significantly via increasing the melt temperature and the packing pressure, but the mechanisms were different. To be specific, the increase of the packing pressure could make more polymer melts fill into the cavity fully. Thus, the density of the micropillars was increased and the filling quality could be improved. The forming rate of frozen layers could be slowed down by increasing the melt temperature. As a result, the purpose of improving the filling quality was achieved. Abstract :